The effects of workload and work-life balance on teacher performance: A meta-analysis study - Lilis Badriah; Widodo Widodo; Merry Lapasau; Hendro Prasetyono; Rozita Che Rodi (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose – This study examines how workload and work-life balance affect teacher performance. Due to these limitations, it is difficult to draw general conclusions about the strength of the relationships among the variables under study. The purpose of this study is to examine in greater depth how workload and work-life balance affect teacher performance by drawing on the findings of previous empirical studies. Method – The study method used meta-analysis to analyze the effects of workload and work-life balance on teacher performance. A systematic search through the DOAJ and Google Scholar databases was conducted. After selection using the PRISMA protocol and inclusion criteria, 14 studies were obtained, consisting of 7 studies on the effect of workload on teacher performance and 7 studies on the effect of work-life balance on teacher performance. A random-effects meta-analysis was performed using JASP and effect sizes were retrieved as correlation coefficients (r). Findings – The results of the meta-analysis indicate that the workload variable has a positive and significant relationship with teacher performance. Work-life balance variable has a positive and significant relationship with teacher performance. These findings underscore the importance of ensuring that teachers’ workloads are distributed proportionally. Teachers’ work-life balance must also be carefully considered in relation to their rights and responsibilities in order to encourage improved teacher performance and thereby continue to enhance the quality of education.